Micronutrient supplement intakes among collegiate and masters athletes: A cross-sectional study - Nichols, Quentin Z.; Ramadoss, Rohit; Stanzione, Joseph R.; Volpe, Stella L. (Frontiers in Sports and Active Living, 2023)
Objective In our cross-sectional study, we evaluated micronutrient supplementation intake among Collegiate and Masters Athletes. Methods We conducted a cross-sectional study to assess micronutrient supplementation consumption in Collegiate and Masters Athletes, comparing sex and sport classification within each respective group. Micronutrient supplement consumption data were measured using a Food Frequency Questionnaire. A two-way analysis of variance was used to explore the differences among Collegiate and Masters Athletes' supplement intakes of the following vitamins and minerals: vitamins A, B6, B12, C, E, D, and calcium, folate, iron, magnesium niacin, riboflavin, selenium, thiamine, and zinc. When significant differences were found, a Bonferroni post hoc test was performed to identify specific group differences. The significance level was set a priori at p < 0.05. Results A total of 198 athletes (105 females and 93 males) were included in the study. Participants were 36.16 ± 12.33 years of age. Collegiate male athletes had significantly greater vitamin A [1,090.51 ± 154.72 vs. 473.93 ± 233.18 mg retinol activity equivalents (RAE)/day] (p < 0.036), folate [337.14 ± 44.79 vs. 148.67 ± 67.50 mcg dietary folate equivalents (DFE)/day] (p < 0.027), and magnesium (65.35 ± 8.28 vs. 31.28 ± 12.48 mg/day) (p < 0.031) intakes compared to Collegiate female athletes. Collegiate CrossFit Athletes (940.71 ± 157.54 mg/day) had a significantly greater vitamin C intake compared to Collegiate General Athletes (156.34 ± 67.79 mg/day) (p < 0.005), Collegiate Triathletes (88.57 ± 148.53 mg/day) (p < 0.027), Collegiate Resistance Training Athletes (74.28 ± 143.81 mg/day) (p < 0.020), and Collegiate Powerlifters (175.71 ± 128.63 mg/day) (p < 0.044). Masters females had significantly greater calcium intakes compared to Masters males (494.09 ± 65.73 vs.187.89 ± 77.23 mg/day, respectively) (p < 0.002). Collegiate Runners (41.35 ± 6.53 mg/day) had a significantly greater iron intake compared to Collegiate Powerlifters (4.50 ± 6.53 mg/day) (p < 0.024). Masters Swimmers (61.43 ± 12.10 mg/day) had significantly greater iron intakes compared to Masters General Athletes (13.97 ± 3.56 mg/day) (p < 0.014), Masters Runners (17.74 ± 2.32 mg/day) (p < 0.03), Masters Triathletes (11.95 ± 3.73 mg/day) (p < 0.008), Masters CrossFit Athletes (15.93 ± 5.36 mg/day) (p < 0.043), Masters Rowers (9.10 ± 3.36 mg/day) (p < 0.003), and Masters Cyclists (1.71 ± 9.88 mg/day) (p < 0.011). Masters Powerlifters (47.14 ± 9.65 mg/day) had significantly greater zinc intakes compared to Masters General Athletes (9.57 ± 2.84 mg/day) (p < 0.015), Masters Runners (10.67 ± 1.85 mg/day) (p < 0.017), Masters Triathletes (10.24 ± 2.98 mg/day) (p < 0.020), Masters Rowers (9.33 ± 2.68 mg/day) (p < 0.013), and Masters Cyclists (1.43 ± 7.88 mg/day) (p < 0.019). There were no other significant differences among the other micronutrient supplement intakes between the sexes or among the sport classification. Conclusion We reported significant differences among female and male Collegiate and Masters Athletes. Additionally, we reported significant differences among Collegiate and Masters Athletes sport classifications. Further research should examine both dietary and micronutrient supplement intake among Collegiate and Masters Athletes to examine the extent that athletes exceed the Recommended Dietary Allowances (RDA), and the potential effects on health and performance.